2011
DOI: 10.1007/s12272-011-0612-3
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and physicochemical characterizations of tanshinone IIA solid dispersion

Abstract: This investigation describes a novel approach to prepare solid dispersions of tanshinone IIA using a laboratory-scale planetary ball mill. Poloxamer 188 was employed as the surfactant carrier to improve the solubility and dissolution of the poorly soluble drug, tanshinone IIA. Solubility and dissolution were evaluated compared to the corresponding physical mixtures and pure drug. Furthermore, the physicochemical properties of the solid dispersions were investigated using scanning electron microscopy, powder X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…[17] and Zhao et al . [15] During scanning of TSIIA/nano-CaCO 3 /poloxamer PMs [Figure 3c], the drug endothermic peak was found at 208.3°C, indicating that the absence of interaction between TSIIA and carriers in PMs and TSIIA existed in a virgin form in the system. In DSC spectra of tSDs [Figure 3d], the characteristic peak of TSIIA had completely disappeared, suggesting that the drug may be present in tSDs as amorphous state, which was responsible for the enhancement of drug dissolution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17] and Zhao et al . [15] During scanning of TSIIA/nano-CaCO 3 /poloxamer PMs [Figure 3c], the drug endothermic peak was found at 208.3°C, indicating that the absence of interaction between TSIIA and carriers in PMs and TSIIA existed in a virgin form in the system. In DSC spectra of tSDs [Figure 3d], the characteristic peak of TSIIA had completely disappeared, suggesting that the drug may be present in tSDs as amorphous state, which was responsible for the enhancement of drug dissolution.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations have been reported by Zhao et al . [15] The FTIR spectrum of carriers showed the peaks at 3487 cm -1 , which corresponded to -OH stretching vibration mode. This could be attributed to the presence of hydroxyl groups and (or) adsorbed water on the surface of nano-CaCO 3 particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Currently, the typical carriers widely used for the formulation of SDs consist of organic materials that are highly water soluble and/or polymeric in nature. [27][28][29][30] In addition to these carriers, inert hydrophilic carriers, such as inorganic silica-based materials 31,32 which have relatively large specific surface areas, and thus produce powders in which the drug may be highly dispersed, are receiving increasing attention. Takeuchi et al [33][34][35] reported that SDs with porous silica or colloidal silica prepared using the spray-drying method can improve the dissolution property of tolbutamide and indomethacin.…”
Section: Introductionmentioning
confidence: 99%
“…Tanshinone IIA (Tan IIA) is a major component of Salvia miltiorrhiza Bunge known as Danshen which has long been used for prevention and treatment of cardiovascular diseases in China (Ren et al, 2010;Zhao et al, 2011;Gao et al, 2012). Accumulating studies show that Tan IIA possesses many biological properties, largely depending on its anti-oxidative effects (Yang et al, 2008;Chen et al, 2012).…”
mentioning
confidence: 99%